FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN DEMAM TYPHOID PADA PASIENN YANG DIRAWAT DI RSU.DR.SOEDARSO PONTIANAK KALIMANTAN BARAT - Nurlaila, Syarifah; Trisnawati, Elly; Selviana, Selviana (JUMANTIK (Jurnal Mahasiswa dan Peneliti Kesehatan), 2014)
Typhoid fever is a systemic infection caused by Salmonella bacteria enteritica, particularly serotype Salmonella typhi. In Pontianak number of patients with typhoid fever each year continues to increase. Based on the annual reports of the RSU. Dr.Soedarso Pontianak, in 2010 the number of new cases of outpatient and inpatient there are as many as 1,180 people by 4 people died, in 2011 amounted to 842 patients with 5 people died, in 2012 amounted to 922 patients with 2 people died. Most of typhoid fever patients aged 5-15 years with a number of cases were 539 patients. The total number of cases of typhoid fever in 2012 ranks second only to diarrhea.This study aims to determine the relationship between water quality household, personal hygiene, the presence Salmoonella typhi on how to wash utensils and cutlery and drinking with the incidence of typhoid fever in hospitalized patients in the RSU dr.Soedarso Pontianak in West Kalimantan in 2014.The design of this study is observational case-control analytic approach then analyzed by chi square test with Î± = 5% (0.05). Stratified random sampling technique sampling the number of respondents was 52 respondents.The results obtained were no relationship between water quality family (p = 0.000), personal hygiene (p = 0.041), the incidence of typhoid fever. while the presence of Salmonella Typhi in cutlery (p = 0.610) showed no association with the incidence of typhoid fever. Techniques washing cutlery and drinking (p = 1.000) showed no association with the presence of salmonella typhi in cutlery.Based on the results of the study are expected RSU.Dr.Soedarso increasing role in providing health education about water quality families who qualify, providing extension of water treatment techniques independently cheap and efisien.Mengadakan education about personal hygiene. For the people should need to increase personal hygiene, especially washing hands properly while before eating, after defecation, regular cut nails of fingers and toes and washing techniques cutlery and drinking to reduce the risk of typhoid fever. For researchers SelanjutnyaDiharapkan can enhance this research by further exploring the factors that can can cause typhoid feverkeyword: typhoid fever, water quality, personal hygiene, washing technique, the presence of Salmonella typhi.